Measuring Mitochondrial Respiration in Previously Frozen Biological Samples. Issue 1 (15th December 2020) - Osto, Corey; Benador, Ilan Y.; Ngo, Jennifer; Liesa, Marc; Stiles, Linsey; Acin‐Perez, Rebeca; Shirihai, Orian S.
Abstract: Measuring oxygen consumption allows for the role of mitochondrial function in biological phenomena and mitochondrial diseases to be determined. Although respirometry has become a common approach in disease research, current methods are limited by the necessity to process and measure tissue samples within 1 hr of acquisition. Detailed by Acin‐Perez and colleagues, a new respirometry approach designed for previously frozen tissue samples eliminates these hurdles for mitochondrial study. This technique allows for the measurement of maximal respiratory capacity in samples frozen for long‐term storage before testing. This protocol article describes the optimal tissue isolation methods and the combination of substrates to define electron transport chain function at high resolution in previously frozen tissue samples. © 2020 The Authors. Basic Protocol 1 : Sample collection, storage, and homogenization for previously frozen tissue respirometry Basic Protocol 2 : Running a Seahorse respirometry assay using previously frozen tissue samples Basic Protocol 3 : Normalization to mitochondrial content for previously frozen tissue respirometry